A Review on Phytochemical and Pharmacological Studies of Fruit Prunus armeniaca Linn.: A Review on Phytochemical and Pharmacological Studies of Fruit Prunus armeniaca Linn. - Lata, Dr. Suman (International Journal of Pharmaceutical & Biological Archive, 2020)
Apricot (Prunus armeniaca Linn.) fruit is good for human health and plays a very important role in our body. Literature studies revealed that apricot fruit has various biological activities such as antioxidant, antibacterial, antimicrobial, anti-inflammatory, and immune-stimulating functions that can be attributed to the content of many phenolic compounds. Apricot fruit contains various phytochemicals such as flavonoids, polyphenols, carotenoids, and phenolic acids by which there are changes in taste, color, and nutritional value of the fruit. The pharmacological studies show that it has anticancer activity which can be validated by clinical trials.